RANCANG BANGUN APLIKASI ABSENSI SISWA BERBASIS WEB PADA SMAN 05 SELUMA DENGAN MENGGUNAKAN KODE QR - Khairullah Khairullah; Yulia Darnita; Marhalim Marhalim; Ari Pitriyo (UNIVED Press, 2024)
The use of information technology has become a key element in improving the quality of educational institutions. By utilizing information technology in improving the teaching and learning process, especially in managing student attendance. The attendance process carried out at SMAN 05 Seluma is still carried out manually which still has several weaknesses, including inefficient manual recording and the risk of data loss. So in this study, it will develop a solution in the form of a student attendance application system that uses QR code technology. The app aims to make attendance management easier by curriculum staff, allow teachers to record student attendance more efficiently, and allow parents to monitor their children's attendance. The main purpose of this application is to record the attendance of students, whether present, sick, or late, as well as generate daily attendance reports as a student guidance tool. The results of the development of this application provide significant benefits, such as assisting teachers and school staff in managing student attendance, reducing suspicion of students, producing useful attendance reports, as well as simplifying the student attendance process and becoming a relevant solution to improve the effectiveness and accuracy of the attendance process at SMAN 05 Seluma, so that it has the potential to improve the quality of education at the school. This research also refers to several related studies that have successfully implemented web-based attendance systems in other educational institutions